High‐strength bimodal ultrafine Ti‐based alloys with enhanced ductility. Issue 5 (28th March 2014) - Cao, G. H.; Zhou, Y. N.; Liu, N.; Li, X.; Russell, A. M.; Gerthsen, D.
<x xml:space="preserve">Abstract</x> Bulk Ti65Fe35 and (Ti65Fe35)96.15‐xSn3.85Nbx (x = 0, 3, 5 and 7 at.%) alloys were prepared by cold crucible levitation melting, and tested in compression at room temperature. The Sn and Nb modified hypereutectic Ti‐Fe alloys exhibited improved mechanical properties under compression. (Ti65Fe35)93.15Sn3.85Nb3 alloy displayed an ultimate compressive strength of 2.7 GPa and a compressive plastic strain of 15%. Electron microscope observations revealed Ti‐Fe(Sn, Nb) alloys having a bimodal microstructure with micrometer‐scale primary TiFe dendrites distributed in an ultrafine eutectic (β‐Ti+TiFe) matrix. The orientation relationship of β‐Ti with TiFe phases is TiFe (011)[100] ∥ β‐Ti (011)[100]. The improved mechanical properties are attributed to the morphology of the phase constituents and the larger lattice mismatches between β‐Ti and TiFe phases due to the additions of Sn and Nb. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>